A tepid alliance: Britain and Turkey in the post-war and early cold war years (Middle Eastern Studies, Special Issue, 'Britain, Turkey and NATO 1945-1960', 2020)
During the transitional period between the end of the Second World War and the beginning of the 1950s London and Ankara left behind the coolness that had crept into their relations as a result of Turkey’s neutrality during the war and reaffirmed their pre-war alliance. However, the strategic interests the two countries shared did not result in a closer political bilateral relationship. Moreover, before long the British government had succeeded by various ill-thought actions in causing the resentment of their Turkish ally. The respective attitudes of the British and the Turks towards each other were informed by the interplay between material interests and ideational factors against the backdrop of the perceived Soviet threat, Britain’s ebbing power and the rising power of the United States. This study narrates a brief but interesting chapter in the course of Turkish-British relations. It also offers interesting insights into the dynamics of great power/small state interaction.